Management of balance problems in an elderly with multiple system atrophy with predominant cerebellar ataxia (MSA-C) and sick sinus syndrome - Eker, Amber; Yigitoglu, Pembe Hare; Duygu, Hamza; Tan, Ersin (Pacini Editore, 2021)
Multiple system atrophy (MSA) is a late-onset, sporadic, progressive, neurodegenerative disorder clinically characterized by autonomic failure and either poorly levodopa-responsive parkinsonism or cerebellar ataxia. There isn't any effective treatment on disease progression. Current therapeutic strategies are primarily based on dopamine replacement and improvement of autonomic failure. Clonazepam, propranolol, baclofen, amantadine, gabapentin, buspirone have also been used for symptomatic treatment of ataxia in MSA patients, but their efficacy known modest and transient. Herein we describe a MSA-C patient with disabling ataxia and sick sinus syndrome who showed distinct improvement in her symptoms after amantadine treatment and cardiac pacemaker implantation.
Keywords: multiple system atrophy; spinocerebellar degeneration; ataxia; amantadine; sick sinus syndrome; gait ataxia